The role of religiosity-spirituality as a moderator between perceived stress and life satisfaction - Rahmat, Hawa; Juhari, Rumaya (Universiti Malaysia Sabah, 2018)
The study examines the role of religiosity-spirituality as a moderator between perceived stress and life satisfaction. There are growing concerns on the study of life satisfaction among young adults especially the undergraduates. It is due to life in the college creates stressful experiences that affect their well-being. It will, in turn, affect their life satisfaction. Stress in the college may lead to several negative outcomes such as depression and physical illness. However, individual differences regarding religiosity-spirituality may affect the way the students cope with the stress. The study on young adult’s religiosity is relevant because of its protective factors, reduce negative behaviour such as smoking and drug abused. Therefore, the study is meant to examine the religiosity-spirituality as the moderating variable between perceived stress and life satisfaction among Malaysian undergraduates. To test the moderating effect, a Multi-group Confirmatory Factor Analysis (CFA) was conducted, since the variable that involved in the study was a latent variable. The results showed that full moderation by Religiosity-spirituality exists on the relationships between the aforementioned variables. Therefore, by extending research on the moderating effect of religiosity-spirituality between perceived stress and life satisfaction among universities students, it will fund valuable input for individual, parents and group intervention, especially for professionals, i.e., counsellors, trainers, and academician. Evidently, religious related variables seemed to play a critical role in determining life satisfaction of the young adult.